The Roles of Batang Public Hospital, HIV Case Manager, People Living with HIV, Partners, and Peer Support Group, in the Prevention of HIV/AIDS Transmission - Dian Kusumawardani; Uki Retno Budihastuti; Mahendra Wijaya (Journal of Health Promotion and Behavior, 2016)
Background: Batang Public Hospital is one of the referal hospitals for People Living with HIV (PLHIV). It provides outpatient and inpatient care service for PLHIV. Batang Public Hospital is expected to play its role as a referal hospital in collaboration with the HIV case manager to provide a comprehensive care to PLHIV, including mobile Voluntary Counseling and Test (VCT), and facilitating HIV/ AIDS peer support group. The study aimed to investigate the dynamic interaction between Batang Public Hospital, HIV case manager, VCT nurse, HIV/ AIDS peer support group, and PLHIV, to prevent and control HIV/ AIDS.Subjects and Method: This was a qualitative study with phenomenology approach, conducted in Batang District, Central Java, Indonesia. Study subjects were selected purposively, which included  PLHIV, VCT nurses, Batang Public Hospital administrators, and HIV case manager. The data were collected by in-depth interview.Result: Batang Public Hospital provides health services with VCT clinics, mobile VCT, PICT (Provider Initiative Counselling and Test), PMTCT (Preventive Mother to Child Transmission). However, PMTCT implementation for birthing mothers with HIV/AIDS is referred to Dr. Karyadi Hospital in Semarang. Batang Public Hospital cooperated with HIV case manager in the implementation of mobile VCT. PLHIV have been participating in the prevention of HIV/AIDS program by using condom.Conclusion: Batang Public Hospital and HIV case manager have been collaborating in the provision of and health social services for PLHIV. Peer support group provide assistant to PLHIV to improve the quality of life. PLHIV have been participating in the prevention of HIV/AIDS transmission program by using condom and playing their role in the PMTCT program.Keywords: PLHIV, health care, peer support group, health behavior, HIV/AIDS case managerCorrespondence: Dian Kusumawardani. Academy of Midwifery Harapan Ibu, Pekalongan, Central Java.Journal of Health Promotion and Behavior(2016), 1(2): 79-86https://doi.org/10.26911/thejhpb.2016.01.02.03